Eating attitudes across body mass index categories in Saudi Arabia: a cross-sectional study - Alzahrani, Hayat; Naseeb, Manal; Zagzoog, Alyaa M.; Malaikah, Sundus; Alsulami, Soaad; Albajri, Eram (Frontiers in Nutrition, 2026)
IntroductionBody weight is linked to disordered eating through psychological, behavioral, and sociocultural mechanisms. Studies in Saudi Arabia reported increased eating disorder risk, particularly among female university students; however, associations between body mass index (BMI) categories and specific EAT-26 subscales remain underexplored. This study assessed eating attitudes among Saudi adults with different BMI categories, examining associations with BMI, and identifying sociodemographic and metabolic risk factors.MethodsThis cross-sectional study surveyed Saudi adults (≥18 years) using convenience sampling via social media between May 30, 2021, and May 22, 2024. Body mass index (BMI) categories were defined as overweight (25.0–29.9 kg/m2) and obesity (≥30 kg/m2). Eating attitudes were assessed using the validated Arabic EAT-26. Multinomial logistic regression examined associations between eating disorder status and BMI categories with sequential adjustment for demographic and health-related factors. Linear and multinomial regression models evaluated relationships between EAT-26 subscales and BMI as continuous and categorical outcomes using SPSS version 27.ResultsAmong 404 Saudi adults, mean BMI was higher in males than females (26.5 ± 5.4 vs. 24.7 ± 5.5 kg·m−2, p < 0.001). In age- and sex-adjusted multinomial logistic regression, participants with a possible eating disorder had a higher relative risk of being overweight compared with normal weight (RRR = 5.90, 95% CI: 1.30–26.83). In linear regression analyses, higher scores for others' perception and oral control were inversely associated with across the full BMI distribution.Discussion/conclusionThese findings underscore the influence of sociocultural change in Saudi Arabia on eating attitudes, where Westernized body ideals and evolving social expectations shape body image concerns. Eating-related attitudes, particularly among individuals in the overweight range, may reflect heightened social sensitivity and self-regulation rather than pathological disordered eating. Culturally sensitive psychosocial screening and stigma-reducing, body-respectful public health strategies may support psychological wellbeing and healthier weight trajectories.